2017
DOI: 10.11336/jjcrs.8.44
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between proximal function of the upper extremity on the paralyzed side and upper extremity skills in daily life of subacute stroke patients

Abstract: The relationship between proximal function of the upper extremity on the paralyzed side and upper extremity skills in daily life of subacute stroke patients. Jpn J Compr Rehabil Sci 2017; 8: 44-50. Objectives: The effects of proximal function of the upper extremity on the paralyzed side on daily life skills were examined in stroke patients. Methods: One hundred and forty-seven stroke patients were evaluated using the Functional Skills Measure After Paralysis (FSMAP), the Finger-Function test (FF), and the Knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
2
0
0
Order By: Relevance
“…Previous studies that used similar Kinect-based VR interventions have reported improvements in the BBT scores [ 35 ] and kinematic hand motion parameters [ 36 ] following intervention in children with HCP. These results are in agreement with the findings of a cross-sectional study on individuals with hemiparesis [ 37 ]. This study found a correlation between the more-affected hand function and active range of motion of proximal segments and suggested that improving the stability and motor control of the more proximal segments seem to be necessary for the promotion of hand skills [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies that used similar Kinect-based VR interventions have reported improvements in the BBT scores [ 35 ] and kinematic hand motion parameters [ 36 ] following intervention in children with HCP. These results are in agreement with the findings of a cross-sectional study on individuals with hemiparesis [ 37 ]. This study found a correlation between the more-affected hand function and active range of motion of proximal segments and suggested that improving the stability and motor control of the more proximal segments seem to be necessary for the promotion of hand skills [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the findings of a cross-sectional study on individuals with hemiparesis [ 37 ]. This study found a correlation between the more-affected hand function and active range of motion of proximal segments and suggested that improving the stability and motor control of the more proximal segments seem to be necessary for the promotion of hand skills [ 37 ]. For instance, a clinical study showed hand function improvements after an electrical stimulation combined with vibration by a reaching robot on the patients’ hemiparetic shoulder.…”
Section: Discussionsupporting
confidence: 93%